Songs of the South: A Song Cycle for Mezzo Soprano and Piano Based on Lyrics from the Heroic Age of Antarctic Exploration - Elizabeth Leane; Carolyn Philpott; McIntryre, S (2014)
Music played an important role in the expeditions of the so-called Heroic Age‚ÄövÑvp of Antarctic exploration (c.1897‚Äö-1922), serving not only to entertain and occupy the men during long periods of idle time, but also to provide motivation to assist with duties such as sledging and perhaps most importantly, to lift their spirits in times of extreme difficulty and uncertainty. The original diaries and published accounts of the expeditions include detailed records of musical events and activities that took place in Antarctica during this period, such as concerts and more regular and informal sing-a-longs,‚ÄövÑvp and some also feature the lyrics of original songs that were composed in Antarctica ‚Äö- on board the vessels, in the huts and tents and/or out on the ice while sledging. Most of these song texts were designed to be sung to a pre- existing tune ‚Äö- often that of a popular song such as a music hall or musical theatre number ‚Äö- and some indicate a specific tune in their subtitles. While most of these song texts are now more than one hundred years old, few of them have ever been set to music or heard outside of the original environment in which they were composed. The focus of this article is on one of the first song cycles to be composed outside of Antarctica that set song texts originating from the expeditions of the Heroic Age ‚Äö- Songs of the South (2014) for mezzo soprano and piano by Australian composer Scott McIntyre (b. 1968). In this article, we explore the historical contexts in which these intriguing song texts were conceived and then examine McIntyre‚ÄövÑvºs approach to setting five of them to music in Songs of the South, including his incorporation of musical quotation and allusion, and his use of compositional devices that had gained currency in Western art music in the period leading up to, as well as during, the Heroic Age of Antarctic exploration, such as the omnibus progression‚ÄövÑvp and serial techniques. Through our discussion of the compositional devices that McIntyre employs in ...